Adaptive Strahlführungen für CO2-Laseranlagen - Neubauer, Norbert (1997)
The aim of this thesis is the development of instructions for the planning of adaptive beam delivery for CO2 laser machines free from optical aberrations. The application of the results leads to the development and application of a processing head with variable focus position during 3D laser beam processing. Within the framework of the thesis a new strategy for the characterization of the beam propagation was developed. A Shack-Hartmann sensor was developed for the measurement of the surface deformation of reflective optics under real conditions in the beam delivery of a laser machine. The results are the input for a consecutive wave optical simulation of the beam propagation. Fundamental investigations of various types of adaptive beam delivery were performed to find the limits for the parameters of adaptive beam delivery. Results include values for the allowed angle of incidence and beam radius at the surface of an adaptive mirror and the accuracy of the mechanical adjustment of the beam delivery. An example for the application of the results is the development of a processing head with variable focus position. In combination with a focal length of the focussing optics of 200 mm a focus shift up to 18 mm is possible. A further application of the results of this thesis is the beam path compensation in industrial laser cutting machines with flying optic